Implications of raising cigarette excise taxes in Peru - Martin Gonzalez-Rozada; Alejandro Ramos-Carbajales
ABSTRACT Objective To assess how raising cigarette excise taxes in Peru might impact cigarette consumption, and to determine if higher taxes would be regressive. Methods Total demand price elasticity was estimated by income groups using two datasets: quarterly time-series data from 1993 - 2012 and data from a cross-sectional survey of income and expenses conducted in 2008 - 2009 . A functional form of the cigarette demand in Peru was specified using the quarterly data set, and the demand price elasticity was estimated for the short and long run. Using the second data set and Deaton methodology, the implementation of elasticity estimation and by groups' elasticity was done in a two-step procedure. Results Demand price elasticity was −0.7, implying that a 10% price increase via a new tax would reduce consumption by 7%. Demand price elasticity estimations by income group suggested that poorer families are not more price sensitive than richer ones, which implies that increasing cigarette taxes could be regressive. Conclusions Increasing cigarette taxes is the most efficient policy for inducing a reduction in smoking. However, in the case of Peru, an increase in cigarette taxes could be regressive.